MODEL EDUKASI UPAYA PENCEGAHAN BULLYING DI SD: STUDI LITERATURE REVIEW - Lilik Mustofiyah; Amalia Noviasari; Dian Wahyuningsih; Early Hari Nugrahini; Choiriyah Widyasari; Ernawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Bullying in primary schools is a major problem that affects students' psychological and academic development. Through a literature review study, This article examines the various educational models that have been used to prevent bullying in primary schools. The educational models used include character education, Social and Emotional Learning (SEL), collaboration-based, media-based, community, whole-school approach, multi-model, and health education. Studies show that a holistic approach involving teachers, parents, students, and the whole school community effectively prevents harassment. Reproductive health education, psychoeducation through videos, role plays, and counseling with lectures and discussions were the education models found to be more effective in preventing harassment. While each model has benefits in increasing students' awareness and understanding of harassment, there are some drawbacks to be aware of. Certain models take a considerable amount of time to implement and require regular psychoeducational support. Therefore, educational models should be tailored to the circumstances and resources available in each school when implemented. To ensure that bullying prevention education is successful, support is needed from various parties, including schools, teachers, education personnel, parents, society, and the community. It is expected that the incidence of harassment in primary schools can be significantly reduced with the right approach and effective cooperation.